Does the efficiency of working capital management and environmental, social, and governance performance affect a firm’s value? Evidence from the United States - Ahmed Mohamed Habib (Financial Markets, Institutions and Risks)
This study evaluates the efficiency of U.S. firms’ working capital management (WCME) by employing the data envelopment analysis technique (DEA). This study uses regression analysis to examine the impact of WCME and environmental, social, and governance (ESGP) performance on U.S. firm value. This study uses a data sample consisting of 964 firm-year observations from a longitudinal panel collected from 2016 to 2019. Endogeneity issues and the employment of additional analyses for robustness were considered. The results indicated that most firms under investigation were relatively inadequate regarding WCME and required correctional efforts by decision-makers to accomplish most reasonable efficiency, directly related to enhancing firm sales and net income. Additionally, the results reveal significant and positive influences of WCME and ESGP on firm value. The implications of this study would push decision-makers to employ the most reasonable procedures and strategies to improve the activities of a firm's WCM and ESG to boost its value and excel in the business environment.